Differences in Learning Methods Start With a Question and Question Student Have Against Social Learning Results Proclamation History Indonesian Independence - Asri, Sriawan; Dwiprabowo, Risky (Universitas Sebelas Maret, 2019)
This study aims to determine whether or not there are differences in the results of social studies learning material on the history of the proclamation of Indonesian independence of students taught by learning methods. Learning Starts With A Question and Question Student Have.Â This study uses a quantitative method with the type of approach